PENGABDIAN MASYARAKAT MELALUI PROGRAM KERJA KKN UNIVERSITAS HINDU INDONESIA DI KELURAHAN UBUNG: PEMBERDAYAAN LINGKUNGAN DAN PENDIDIKAN KARAKTER - Sanjaya, Kadek Oky; Gede, I Komang; Utama, Made Alit Wirya; Novianti, Ni Kadek; Widiantari, Ni Kadek Arsitalia (JURNAL SEWAKA BHAKTI, 2025)
Community Service Program (KKN) is a concrete implementation of the Tri Dharma of Higher Education, particularly in the field of community service. Through KKN activities, students are expected to be able to apply the knowledge and skills acquired during lectures to provide solutions to real problems in the community. KKN Group 1 of the Indonesian Hindu University was implemented in Ubung Village, North Denpasar District, from August to September 2025. This program emphasized increasing public awareness of environmental cleanliness, waste management, community empowerment through women's farmer group (KWT) activities, and character education in elementary schools. The main activities carried out included the creation and installation of waste education signs, stop bullying socialization, diligent savings socialization, making retrace bins from recycled waste, making bio pore holes, and providing eco-bags to residents as a medium for managing household waste. The implementation of activities was carried out with a participatory approach, involving the community, village officials, and educational institutions. The results of the activities showed an increase in community participation in cleaning activities, increased awareness of household waste management, and the growth of a spirit of mutual cooperation and social awareness in the Ubung community.